Comparison of asymmetric (low morning-dose) and standard split-dose regimen of PEG plus bisacodyl for bowel preparation: A randomized controlled trial. Issue 6 (June 2019) - Andreozzi, Paolo; De Nucci, Germana; Bezzio, Cristina; Arena, Ilaria; Devani, Massimo; Mandelli, Enzo; Morganti, Daniela; Omazzi, Barbara; Reati, Raffaella; Redaelli, Davide; Saibeni, Simone; Manes, Gianpiero
Abstract: Background: Reducing the morning dose of PEG solution may be a reliable strategy to improve the patient compliance of split-dose regimens without affecting efficacy of bowel cleansing. Aims: to compare the efficacy for bowel cleansing of an asymmetric split-dose regimen (25% of the dose on the day of colonoscopy and 75% on the day before) with the standard split-dose regimen. Methods: Outpatients were enrolled in a randomized, single-blind, non-inferiority clinical trial. All subjects received a split-dose preparation with a 2L PEG-citrate-simethicone plus Bisacodyl. Patients were randomly assigned to: group A, asymmetric split-dose regimen; group B, symmetric split-dose regimen. Primary endpoint was the proportion of adequate bowel cleansing. Results: Split-dose was taken by 81 and 80 patients in group A and B. Adequate bowel cleansing was achieved in 92.6% and 92.5% patients in group A and B (p = 1.000). No differences were observed regarding Boston Bowel Preparation Scale total score, adenoma detection rate and scores of each colon segment. Conclusions: The reduction of morning dose of PEG in a split-dose regimen is not inferior to the standard split-dose regimen in achieving an adequate bowel cleansing. However, further studies are needed to evaluate whether asymmetric preparation is associated to a higher tolerability compared to symmetric split-dose regimen. (NCT03146052)